"FUTURE ARENAS" AS AN ENVIRONMENT FOR IMPLEMENTING TRANSFORMATION PROCESSES: POTENTIAL AND LIMITATIONS OF DIGITALIZATION IN A HYPERCOMPETITION CONDITION - OLIYNYK, KYRYLO (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The research is based on the hypothesis that modern digital technologies, which embody the digital revolution, have a decisive influence on the formation of the future digital reconfiguration of the global economy. The Internet of Things allows to create adaptive, smart, efficient goods and services. Depending on the ability of a person, consumer, entrepreneur to use its potential, digital technology can acquire features both transformative, initiating the creation of new industry niches/growth points and rethinking existing business models, and destructive, leading to the loss of market positions. Any company that seeks to use digital technologies must be ready to adapt its strategies in the process of generating new approaches to value creation. The purpose of the article is to analyze promising economic, innovative production areas (arenas), which in the future are capable of generating the lion's share of added value in the global economy, transforming competitive relations and the established market conditions of goods and services under the influence of digitalization. The leadership structure in "arenas" is extremely dynamic: they are characterized by sharp significant changes in investment growth; high profitability provokes competition, exacerbating it, in already competitive innovation markets. In some "arenas" growth can be achieved on the basis of various factors (competitive advantages), for example: through the improvement of technologies (growth of technological potential); by increasing resource potential and more efficient use of resources; on the basis of increased management efficiency and information support; through an improvement in the quality of human potential.This causes sharp changes in technologies and business models, which leads to a rapid change of leaders.The industrial revolution is the driver of a qualitative leap in the improvement of production management methods and forms, the formation of a new structure of social production, the development of productive forces, a greatly increasing role of the human factor, an increase in the importance of world economic relations, and, as a result, the transformation of technological structures. It is a certain sum of innovations of various natures, each of which contains a chain of interacting principles and technologies of organization, which are a strong "trigger" for the future productivity of different types of economic activity. "Arenas of the future" will be characterized by an exponential acceleration of technology development, which leads to a sharp increase in their productivity; convergence of technologies and synergy of their general use; a sharp decrease in the cost price and, accordingly, the price of products, equipment, devices, services based on the use of modern digital, bio, nano, and other technologies; the importance of super platforms – the Internet and satellite navigation systems, which provided the conditions for expanding the effects of digitalization and reaching a new level of interconnectedness, which stimulated the acceleration of commercialization of innovations and technological progress, simplification and expansion of access to modern technologies, the formation of new businesses around the world; reduction of R&D costs and entry into the market of innovative start-ups in the context of increased availability of new technologies, a sharp reduction in initial costs for necessary services, equipment, etc. The emergence of "arenas" presupposes the development of new forms of cooperation between the state and the private sector. Many of the "arenas of the future" are unaffordable for private investors, as they presuppose a very long-term planning horizon, requiring the construction of a closed cycle - from personnel training to product servicing. This is why leading countries are already implementing state programs in the field of advanced industrial technologies, designed to manage the new technological revolution and radically strengthen competitive positions in the global market. This will further increase inequality in the technological sphere.
Keywords: global transformations; digital transformations; digital revolution; technological development; innovative development; innovation; world economy; competition; digital ecosystem; arena; AI; Internet; capitalization; technology company